Itu Pengembangan Modul Gelombang Bunyi Berbasis Model Pembelajaran CPS untuk Meningkatkan Kemampuan Berpikir Kreatif dan Motivasi Belajar Peserta Didik SMA - Siti Wulan Sari; Azhar Azhar; Zulirfan Zulirfan (Jurnal Penelitian Pendidikan IPA, 2023)
This examination plans to deliver a sound wave module in light of the CPS learning model that is reasonable for use in the secondary school/Mama physical science educational experience. The sort of exploration utilized is improvement research (R&D) with the ADDIE model (Analyze, Plan, Advancement, Execution, Assessment). The examination instruments utilized were approval sheets and reaction sheets for instructors and understudies with a size of four likerts given to 3 specialists, 3 educators, and 26 understudies of SMA Negeri 1 Kampar Timur. The information was examined quantitatively founded on the aftereffects of master approval, educator, and understudy reactions. The aftereffects of approval utilizing the typical score directed by three master validators were in the Substantial classification with a typical score of material specialists of 3.67, educational specialists a typical score of 3.53, and media specialists a typical score of 3.60. The reaction of educators from 3 instructors got a typical educator reaction score of 3.71 and was in the generally excellent classification and the members' reaction got a typical understudy reaction score of 3.62 with an excellent classification. In light of the information acquired, the sound wave module given the CPS learning model is substantial and appropriate for use in the secondary school material science growing experience.